Association between somatic cell count early in the first lactation and the longevity of Irish dairy cows - Archer, Simon C.; Mc Coy, Finola; Wapenaar, Wendela; Green, Martin J. (American Dairy Science Association, 2013)
Reduced longevity of cows is an important component of mastitis costs, and increased somatic cell count (SCC) early in the first lactation has been reported to increase culling risk throughout the first lactation. Generally, cows must survive beyond the first lactation to break even on their rearing costs. The aim of this research was to assess the association between SCC of primiparous cows at 5 to 30 days in milk (SCC1), and survival over a 5-y period for cows in Irish dairy herds. The data set used for model development was based on 147,458 test day records from 7,537 cows in 812 herds. Cows were censored at their last recording if identified at a later date in other herds or if recorded at the last available test date for their herd, otherwise, date of disposal was taken to be at the last test date for each cow. Survival time was calculated as the number of days between the dates of first calving and the last recording, which was split into 50-d intervals. Data were analyzed in discrete time logistic survival models that accounted for clustering of 50-d intervals within cows, and cows within herds. Models were fitted in a Bayesian framework using Markov chain Monte Carlo simulations. Model fit was assessed by comparison of posterior predictions to the observed disposal risk for cows aggregated by parameters in the model. Model usefulness was assessed by cross validation in a separate data set, which contained 144,113 records from 7,353 cows in 808 herds, and posterior predictions were compared with the observed disposal risk for cows aggregated by parameters of biological importance. Disposal odds increased by a factor of 5% per unit increase in ln SCC1. Despite this, posterior predictive distributions revealed that the probability of reducing replacement costs by >€10 per heifer calved, through decreasing the herd level prevalence of cows with SCC1 ≥400,000 cells/mL (from an initial prevalence of ≥20 to <10%) only exceeded 50% for less than 1 in 5 Irish herds. These results indicate that the effect of a reduction in the prevalence of cows with SCC1 ≥400,000 cells/mL on replacement costs alone for most Irish dairy herds is small, and future research should investigate other potential losses, such as the effect of SCC1 on lifetime milk yield.